2021
DOI: 10.30872/psikostudia.v10i1.4583
|View full text |Cite
|
Sign up to set email alerts
|

Moderasi Usia dalam Pengaruh Semester Terhadap Efikasi Diri Akademik pada Pembelajaran Online

Abstract: Penyebaran virus corona menuntut institusi pendidikan untuk melaksanakan pembelajaran online. Tujuan penelitian ini untuk menjelaskan pengaruh semester terhadap efikasi diri akademik pada pembelajaran online dan menjelaskan moderasi usia dalam pengaruh semester terhadap efikasi diri akademik pada pembelajaran online. Subjek dalam penelitian ini berjumlah 296 mahasiswa yang dipilih dengan teknik incidental sampling. Metode penelitian yang digunakan dalam penelitian ini yakni kuantitatif korelasional. Hasil pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The relationship test shown in Table 2 resulted in a correlation relationship between age and education level (0.000), with a strength level of 0.852 which is very strongly correlated; this is said to be true because, based on daily life, generally the older the age, the higher the level of education that is being taken and lived will be higher 32 . However, this does not show that the older the age and higher education taken, the more good nutritional knowledge, including in vegetable and fruit knowledge, because in the correlation test it was found that the age and level of education did not show any relationship with the level of knowledge of vegetable and fruit nutrition (0.922 and 0.391).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship test shown in Table 2 resulted in a correlation relationship between age and education level (0.000), with a strength level of 0.852 which is very strongly correlated; this is said to be true because, based on daily life, generally the older the age, the higher the level of education that is being taken and lived will be higher 32 . However, this does not show that the older the age and higher education taken, the more good nutritional knowledge, including in vegetable and fruit knowledge, because in the correlation test it was found that the age and level of education did not show any relationship with the level of knowledge of vegetable and fruit nutrition (0.922 and 0.391).…”
Section: Resultsmentioning
confidence: 99%
“…Bandura (1997) menjelaskan bahwa efikasi diri adalah hasil dari proses kognitif seseorang berupa keputusan, keyakinan, atau pengharapan tentang bagaimana individu memperkirakan kemampuan dirinya dalam melaksanakan tugas atau tindakan tertentu untuk mencapai hasil yang diinginkan (Ghufron & Risnawita S, 2012). Menurut penelitian Halawa (2020) tentang self efficacy mahasiswa dalam belajar pada masa pandemi Covid-19 di STIKes William Booth menunjukkan bahwa sebanyak 68 responden (66%) memiliki self efficacy tinggi karena mahasiswa sudah memiliki pengalaman belajar di kampus tersebut dan sudah mengenal para staf dosen, dan sudah mengetahui bagaimana cara mengatasi hambatan-hambatan atau masalah dalam proses pembelajaran dalam jaringan Pada penelitian Pantu (2021), tentang moderasi usia dalam pengaruh semester terhadap efikasi diri akademik pada pembelajaran online, dijelaskan bahwa terdapat pengaruh negatif yang signifikan dari semester terhadap self efficacy selama pembelajaran daring. Hasil penelitian ini menjelaskan bahwa semakin tinggi semester maka semakin rendah self efficacy yang dimiliki.…”
Section: Pembahasan a Analisa Univariat A Self Efficacyunclassified
“…Pada penelitian Pantu (2021), tentang moderasi usia dalam pengaruh semester terhadap efikasi diri akademik pada pembelajaran online, dijelaskan bahwa terdapat pengaruh negatif yang signifikan dari semester terhadap self efficacy selama pembelajaran daring. Hasil penelitian ini menjelaskan bahwa semakin tinggi semester maka semakin rendah self efficacy yang dimiliki.…”
Section: Pembahasan a Analisa Univariat A Self Efficacyunclassified
“…Part of a nursing supervisor's duties is to ensure the quality of their staff's work 5,6. The application of a transformational leadership style can improve the patient safety culture and lead to better management of nursing resources 7-9…”
mentioning
confidence: 99%
“…5,6 The application of a transformational leadership style can improve the patient safety culture and lead to better management of nursing resources. [7][8][9] Another factor related to selfefficacy is experience. The more mature an employee, the better their self-efficacy, because sufficient experience often means that they are better at solving problems.…”
mentioning
confidence: 99%